Effects of extracts from goji berry (Lycium barbarum), green tea (Camellia sinensis), and persimmon (Diospyros kaki) leaves in a dry eye model of mice - Basa, Alper; Canpolat, Ibrahim; Kulualp, Kadri; Aslan, Abdullah; Eroksuz, Yesari; Cakir-Bayrak, Sema; Gokdere, Gokhan (Univ Nacional Autonoma Mexico Facultad Medicina Veterinaria Zootecnia, 2025)
This study aimed to investigate the effects of goji berry (Lycium barbarum) [GB], green tea (Camellia sinensis) [GT], and persimmon (Diospyros kaki) [DK] leaf extracts in a mouse dry eye (DE) model. Fifty-six eyes from 28 female BALB/c mice were equally divided into the following groups: control, GB, GT, and DK (left eye groups); DE, DE + GB, DE + GT, DE + DK (right eye groups). The DE model was induced in right eye groups by topical administration of 5 mu L of 0.2 % benzalkonium chloride twice daily for 14 days. A 1 % extract solution of GB, GT, and DK was instilled in the DE + GB, DE + GT, and DE + DK groups between days 15 and 30, respectively. In the DE group, only 0.9 % NaCl was instilled during this period. All groups were evaluated for aqueous tear production rate, corneal fluorescein staining, and tear breakup time (TBUT). Histopathological and Western blot analyses performed after euthanasia. On day 15, aqueous tear production decreased, corneal fluorescein staining scores increased, and TBUT was shortened in right eye groups compared to left eye groups (P < 0.05). At the end of the study, no significant differences were observed among the extract-treated DE groups regarding clinical parameters (P > 0.05). However, based on histopathological and molecular analyses, the GT group demonstrated the most beneficial effect without side effects (P < 0.05). These results suggest that 0.1 % GT leaf extract may be a potential therapeutic agent for DE.
Keywords: Dry eye; Inflammation; Phytotherapy; Precorneal Tear Film; Tear hyperosmolarity; Treatment